Experimental Research on Quarry Wastewater Purification Using Flocculation Process - Yongjie Bu; Kangjian Zeng; Heng Yang; Aihui Sun; Qingjun Guan; Shuang Zhou; Wenqing Peng; Weijun Wang; Peng Ge; Yue Yang (Molecules)
The flocculation-based purification of quarry wastewater continues to pose a significant challenge in mineral processing and environmental engineering, primarily due to persistent turbidity issues and inefficient floc settling behaviour. In this study, we systematically investigate the synergistic effects of organic and inorganic flocculants to reduce turbidity and improve floc settling performance. Through a series of optimised experiments using polyaluminium chloride as an inorganic flocculant, polyacrylamide as an organic flocculant, and calcium oxide as a pH regulator agent, the treatment efficiency was evaluated. Under the optimal conditions with 200 g/m3 CaO as the regulator agent and 2.5 g/m3 PAC and 12 g/m3 PAM as flocculants, the residual turbidity was reduced to 97.30 NTU, meeting stringent industrial discharge standards and enabling zero-discharge water reuse. Zeta potential measurements, optical microscopy, and DLVO theory collectively elucidated the interfacial interactions between flocculants and mineral particles, with zeta potential revealing electrostatic effects, microscopy visualising aggregation patterns, and DLVO theory modelling revealing colloidal stability, thereby mechanistically explaining the enhanced aggregation behaviour.